Uji Sitotoksik Ekstrak Alkaloid Daun Belimbing Wuluh (Averrhoa bilimbi L.) terhadap Larva Udang (Artemia salina) - Mariani Mariani; Kholifatu Rosyidah; Kamilia Mustikasari (Universitas Lambung Mangkurat, 2021)
Research on cytotoxic test of alkaloids extract of belimbing wuluh leaves has been conducted. The objective of this research are to determine the yield, toxicity, TLC chromatogram pattern, and compounds in alkaloids extract of belimbing wuluh leaves with GC-MS. Alkaloid extraction process uses acid base method, the phytochemical tests was carried out with reagents Dragendorff, Wagner and Meyer. Toxicity test of alkaloids extract of belimbing wuluh leaves with BSLT method on A. salina larvae to determine LC50 value. Alkaloids extract of belimbing wuluh leaves were analyzed by TLC and GC-MS. The yield of alkaloids extract of belimbing wuluh leaves obtained was 10, 13 %. The results of phytochemical tests were carried out which showed positive containing alkaloids. LC50 value of the alkaloids extract of belimbing wuluh leaves indicated that is very toxic. The LC50value obtained is 9.170 ppm. Analysis using TLC with eluent of n-hexane: ethyl acetate (8:2) showed 5 stains. GC-MS analysis showed are alkaloid compound with an odd molecular weight.